Evaluation of the clinical efficacy of the suspension to reduce the hypersensitivity of dental hard tissues with arginine and calcium phosphate (Эндодонтия Today)
Hypersensitivity of dental hard tissues is a common, independently existing, and concomitant diseases of dental system. The aim of the work was to evaluate the clinical efficacy of the drug on the basis of 8% arginine and calcium phosphate («Desensetin» suspension). Results of the study showed the clinical efficacy of the drug «Desensetin» in the clinic treating hyperesthesia of hard dental tissues.